2018
DOI: 10.1016/j.wocn.2018.07.002
|View full text |Cite
|
Sign up to set email alerts
|

Perceptual categorization and bilingual language modes: Assessing the double phonemic boundary in early and late bilinguals

Abstract: The experimental procedures utilized in the present study have been approved by a Human Subjects Protection Program supervised by an Institutional Review Board. All participants signed an informed consent form prior to their participation in the tasks reported in the present study. The authors declare that they do not have any conflicts of commitment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 61 publications
(136 reference statements)
4
28
0
Order By: Relevance
“…We only had data for an L2 contrast and, thus, it is possible that our cohort of bilinguals favored English over Spanish. It is also possible that the robust L2 speech processing indicated that the early bilinguals we tested were able to adjust their phonological contrasts based on linguistic contexts (see Casillas & Simonet, 2018). We did not attempt to manipulate context, and the experimental setting decidedly favored English, with the consent and instructions carried out in English.…”
Section: Discussionmentioning
confidence: 99%
“…We only had data for an L2 contrast and, thus, it is possible that our cohort of bilinguals favored English over Spanish. It is also possible that the robust L2 speech processing indicated that the early bilinguals we tested were able to adjust their phonological contrasts based on linguistic contexts (see Casillas & Simonet, 2018). We did not attempt to manipulate context, and the experimental setting decidedly favored English, with the consent and instructions carried out in English.…”
Section: Discussionmentioning
confidence: 99%
“…First, as was noted elsewhere, future research should include both discrimination and identification tasks because those tasks may tap into different perceptual skills involved in different stages of perceptual learning. Likewise, it would be beneficial to control for language mode within the study, encouraging L2 processing by providing materials and instructions in the L2 whenever possible, given that even novice learners may demonstrate dual perceptual boundaries (Casillas & Simonet, 2018; Gonzales, Byers‐Heinlein, & Lotto, 2019). With respect to the production tasks, the participants in the present study may have been able to use the auditory form presented during delayed repetition to enhance their production.…”
Section: Limitations and Future Directionsmentioning
confidence: 99%
“…Previous studies have used perceptual cues, including conversations, videos, and/or magazines to create influential language contexts in bilinguals’ speech perception (Antoniou et al, 2012; Casillas & Simonet, 2018; Elman et al, 1977; Flege & Eefting, 1987a; García-Sierra et al, 2009; 2012; Gonzales & Lotto, 2013; Hazan & Boulakia, 1993). However, this design cannot disambiguate if the bottom-up properties, or rather the top-down conceptual knowledge, provided by the perceptual cues themselves primarily influenced the observed double phonemic boundary effect.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Other investigations have shown that bilinguals remain sensitive to the linguistic properties of perceptual cues and preferentially tailor speech processing towards the most appropriate language (Casillas & Simonet, 2018; Gonzales & Lotto, 2013; Ju & Luce, 2004; Lagrou, Hartsuiker & Duyck, 2011). In an eye-tracking paradigm targeting bilinguals’ lexical access, Ju and Luce (2004) presented highly proficient Spanish–English bilinguals four pictures of objects along with a spoken Spanish target word that always began with a voiceless stop consonant (i.e., /p, t, k/).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation